Religious tension and tolerance in Malaysia: a survey of newspaper reports on religious tension incidents from 1997-2003 - Muhamad Shukri, Abdul Salam (Institut Kefahaman Islam Malaysia (IKIM), 2004)
Malaysia being a multi-racial and multi-religious society has the unique honour of being the home of many religions and races of people. Based on this multi-dimensional nature of Malaysia and its constitution recognition of a particular religion as the official religion in the midst of many others, even though these other religions are practiced by the minority in the country, one would expect that there should be, and certainly would be a religious tension in the country as in other countries of the same nature like Malaysia. Moreover, since there was a crisis of this nature on the 13th of May 1969, in which there was a racial cum religious riot, which resulted in the death of a number of people, it is worthwhile to look into what is happening now and to now if this kind of tension still exist or not. Thus based on this assumption and on the fact that a thing of this nature has happened before in this nation, this article makes a survey of major newspaper reports on religious crisis in the country between the periods of 1997 to 2003 in order to ascertain whether religious tension still continue to exist in the country or not. And if it does not exist anymore, what are the modalities or factors responsible for its non-existence? The methodology that would be employed is both empirical and analytical in nature. The empirical method would be employed in the gathering of data from the major newspaper reports in Malaysia during the period under study and likewise in other foreign media reports which carried some news related to the issue under discussion, while the analytical methodology would be employed in the analysis of these data gathered from the newspapers. To sum up, this study found out that the religious tension during this period, though very serious, did not balloon into a major crisis as it was effectively contained and control by the government and the will of the majority of the people.